Answer:x f(x) = 2.5x − 10.5 g(x) = 64(0.5x)
2 f(2) = 2.5(2) - 10.5 g(2) = 64(0.5*2)
f(2) = 5 - 10.5 g(2) = 64(1)
f(2) = -5.5 g(2) = 64
3 f(3) = 2.5(3) - 10.5 g(3) = 64(0.5*3)
f(3) = 7.5 - 10.5 g(3) = 64(1.5)
f(3) = -3 g(3) = 96
4 f(4) = 2.5(4) - 10.5 g(4) = 64(0.5*4)
f(4) = 10 - 10.5 g(4) = 64(2)
f(4) = -0.5 g(4) = 128
5 f(5) = 2.5(5) - 10.5 g(5) = 64(0.5*5)
f(5) = 12.5 - 10.5 g(5) = 64(2.5)
f(5) = 2 g(5) = 160
6 f(6) = 2.5(6) - 10.5 g(6) = 64(0.5*6)
f(6) = 15 - 10.5 g(6) = 64(3)
f(6) = 4.5 g(6) = 192